Analysis of The Effect of Funding Strategy on The Company’s Financial Performance at PT Jasamarga Transjawa Tol - Sanusi, Amri; Anas, Eka Pria (Syntax Literate, 2024)
This research aims to investigate the implications of funding strategies employed by PT Jasa Marga and its subsidiary PT Jasamarga Transjawa Tol on their financial performance. With the Indonesian government's increased investment in toll road infrastructure, Jasa Marga, a State-Owned Enterprise, has undertaken expansive endeavors, augmenting investments from IDR 24.8 trillion in 2018 to IDR 78.6 trillion by 2022. However, this escalation in investment levels also brings forth heightened liabilities, predominantly stemming from reliance on debt, particularly bank loans, in addition to equity. Such a scenario presents challenges in managing payment obligations and, if not handled adeptly, could imperil Jasa Marga's financial performance. Consequently, strategies aimed at bolstering the company's capital structure are slated for implementation in 2023. This exploration aims to assess how these financial strategies and the debt-equity balance influence company value and financial health, drawing on frameworks like the Pecking Order Theory. It seeks to comprehend the ramifications of internal and external financing on the company's solvency, as measured by ratios such as Debt Equity Ratio (DER), Debt Ratio, and Interest Coverage Ratio (ICR). The literature review delves into various financial strategies such as crowdfunding and Initial Public Offering (IPO), elucidating their motivations and repercussions on companies, with a specific focus on aspects like information asymmetry and changes in post-IPO performance. This research integrates theories, practical strategies, and financial metrics to derive meaningful, data-driven conclusions aimed at optimizing capital structure and enhancing financial stability. It offers valuable insights to stakeholders and facilitates improved financial decision-making processes within the company.